Analisis Menjaga Kebersihan Wisata Khususnya Di Daerah Pesisir Dan Pantai - Sindy C Tumurang; Melky Pangemanan; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The cleanliness of tourist destinations, especially in coastal and beach areas, is a crucial aspect that supports environmental sustainability and visitor comfort. This study analyzes various strategies and best practices for maintaining cleanliness in coastal tourist areas. The research methods used include literature review, field observations, and interviews with tourism managers, visitors, and local communities. The findings indicate that active participation from all stakeholders, including the government, community, and tourists, is essential in maintaining cleanliness. Additionally, environmental education, adequate sanitation facilities, and strict regulation enforcement significantly contribute to the cleanliness of coastal areas. The study concludes that a holistic and collaborative approach is key to preserving the cleanliness and beauty of coastal and beach tourist destinations.